Navigating Climate Policies Amidst the Realities of Rice Self-Sufficiency in Indonesia - Ariva Permana; Chantamon Potipituk (My University, 2024)
Rice self-sufficiency is a central goal for the Indonesian government, providing significant political benefits. However, achieving this goal is challenging due to the heavy reliance of rice production on water availability, which climate change can significantly alter. Our study investigates the relationship between Indonesia’s climate change policies and rice prices, considering the paradox of rice self-sufficiency. We hypothesize a correlation between climate policy and rice prices, assuming market forces primarily determine prices. Our findings reveal an unexpected result: there is no strong, direct correlation between local climate policy and rice self-sufficiency in Indonesia. This suggests that the dynamics of rice production and pricing may be influenced by other factors, particularly government interventions, warranting further investigation. These insights highlight the complexities in balancing climate strategies with agricultural goals in Indonesia.
Keywords: Self-sufficiency; Economic Growth and Fiscal Policies